PTH-076 Establishing a Clostridium difficile management team: 1-year results post-implementation. (23rd September 2015) - Gupta, S; Mathew, S; Twagira, M; Vig, S; Lim, S; Watts, S; Hawkes-reekes, J; Nicholson, D; Adisi, J; Glasgow, A; Graham, J; Chaffer, D
Abstract : Introduction: A Clostridium difficile Management Team was created at Mayday University Hospital in October 2008 in accordance with HPA (Health Protection Agency) guidance.1 It consists of a Consultant Gastroenterologist, as well as three other Consultants (Elderly Care, Surgical and Microbiology), four Clinical Nurse Specialists, an Antibiotic Pharmacist and a Dietician, working across the directorates. The Team reviews all patients with C.difficile infection and also implements infection control measures. We report our progress at 1-year post initiation. Methods: All patients diagnosed with C difficile infection from October 2007 to October 2009 were included. These were classified as either Hospital Acquired Infections (HAIs) or Community Acquired Infections (CAIs). Information on deaths due to C difficile (either directly linked, or as a contributory factor) were extracted from the infection control surveillance system over the same period. Results: A total of 540 C difficile cases were identified from January 2007 to October 2009. 330 HAIs occurred in the 21 months before intervention, averaging 16 cases/month. This fell to 5 cases/month in the intervention year from October 2008 to Oct '09 (a 69% reduction). CAI rates averaged 6/month in 2007, and 3/month in 2008, and remained unchanged at 3/month in the intervention year. Mortality figures showed 24 deaths in the 21 months pre-introduction, and 6 deaths in the intervention year (a 57% reduction compared to the preceding October 2007 to Oct '08). Conclusion: Utilising a multidisciplinary team in the management of Clostridium difficile infection is recommended by the HPA.1 Our dedicated team focuses on optimising care, as well as ensuring the isolation and prompt clinical and laboratory diagnosis of suspected cases. The team also provides education to hospital staff and General Practitioners. This, together with other existing measures1 3 such as restrictive antibiotic prescribing, chlorine-based environmental cleaning and effective hand hygiene promotion has had a significant effect in reducing the burden of C difficile in our Trust.